Predicting Failure Tolerance and Irrational Beliefs of Female Students based on the Use of Social Networks - Masoomeh Mehdipoorsani; Alireza Aghaz; Masoud Ghasedi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2022)
Aim and Background: The use of social networks (USN) is very common among students. Excessive USN can negatively affect their psychosocial performance. Students' health is affected by the amount of use of social networks. Uncontrolled USN affects people's social, academic and professional life. The purpose of this research was to determine the relationship between the USN with failure tolerance and irrational beliefs in female students. Methods and Materials: The present study was a cross-sectional descriptive study. The statistical population of the study is all female students in Azad university of Tehran, Saveh and Tonekabon in year of 2020-2021. 240 female students were selected using the available sampling method. The Irrational beliefs questionnaire, failure tolerance questionnaire, and virtual networks tendency questionnaire were used. Data were analyzed using Pearson's correlation coefficient and regression analysis using the SPSS version 25. Findings: There was a negative relationship between the USN and failure tolerance (r=0.70, P<0.001). There was a positive relationship between the USN and irrational beliefs (r=0.80, P<0.001). The results of multiple regression showed that the amount of the USN has the ability to predict 33.3% failure tolerance and 53.9% irrational beliefs of female students. The type of the USN can predict 29.4% of failure tolerance and 49.2% of irrational beliefs of female students. Also, the level of trust of users has the ability to predict 24.4% of failure tolerance and 49.9% of irrational beliefs of female students (P<0.05). Conclusions: Problematic and excessive use of online social networks can endanger students' physical and mental health by increasing irrational beliefs and reducing failure tolerance. Therefore, education and culture building in the field of optimal use of online social networks is necessary during student life.